PENINGKATAN KEWIRAUSAHAAN DAN OPTIMALISASI UNIT USAHA PESANTREN UNTUK KEMANDIRIAN EKONOMI: STRATEGI DALAM MENGHADAPI TANTANGAN GLOBAL - Alkhan, Muhammad Hayyi Lana; Valeriani, Devi; Akbar, Muhammad Faisal; Wulandari, Ayu; Rahmani, Zikri; S, M. Afdal; Fauzi, Ahmad (Jurnal Abdi Insani, 2026)
Pondok Pesantren Al-Islam Kemuja plays an important role in Islamic education and community empowerment, particularly in developing entrepreneurship based on the pesantren economic model. However, the optimization of the pesantren’s business units still faces several challenges, such as limited access to capital, a lack of business mentoring, and minimal utilization of digital technology for marketing and sharia-based transactions. These challenges hinder the pesantren’s efforts to achieve optimal economic independence, compounded by restricted funding and insufficient entrepreneurship training for both students and pesantren managers. The aim of this program is to formulate strategies to strengthen entrepreneurship and optimize the pesantren’s business units to achieve economic independence through sharia-based business management training and the use of digital technology. The implementation method began with a preliminary survey to analyze the conditions and needs of the pesantren. This was followed by entrepreneurship and sharia-based business management training, and subsequently the application of the training outcomes within the pesantren’s business units to enhance economic independence and operational efficiency. The results of this program include improved managerial skills among pesantren administrators in professionally managing business units. The entrepreneurial capacity of the students also increased through the provided training. Additionally, the program successfully enhanced the use of digital technology in marketing and sharia-compliant transactions. The sustainability of the pesantren’s economy has become more assured through the optimization of more efficient and sustainable business units. Pondok Pesantren Al-Islam Kemuja has now implemented more structured and sharia-based entrepreneurial strategies, contributing to the improvement of the pesantren’s economic independence.